2005
DOI: 10.3168/jds.s0022-0302(05)72768-5
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Dry Period Length to Simplify Feeding Transition Cows: Milk Production, Energy Balance, and Metabolic Profiles

Abstract: Sixty-five Holstein cows were used to evaluate management schemes involving altered dry period (DP) lengths on subsequent milk production, energy balance (EB), and metabolic variables. Cows were assigned to one of 3 treatments: traditional 56-d DP (fed a low-energy diet from -56 to -29 d and a moderate energy diet from -28 d to parturition; T), 28-d DP (continuously fed a high energy diet; S), and no planned DP (continuously fed a high energy diet; N). Prepartum DM intake (DMI), measured from 56 d prepartum th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

55
308
9
10

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(382 citation statements)
references
References 37 publications
(63 reference statements)
55
308
9
10
Order By: Relevance
“…Eckles and Palmer (1916) concluded that heat-coagulable protein content of colostrum is reduced remarkably as DPL was reduced (n 5 4). Negative impacts of CM on IgG and protein content of colostrum have been reported in the literature (Brandon and Lascelles, 1975;Remond et al, 1997b;Rastani et al, 2005). Guy et al (1994) demonstrated that prepartum milking of udder halves resulted in less concentration of IgG 1 in secretions of milked glands than in dry glands from 10 days prepartum to 1 day postpartum.…”
Section: Altered Dry Periodsmentioning
confidence: 89%
See 2 more Smart Citations
“…Eckles and Palmer (1916) concluded that heat-coagulable protein content of colostrum is reduced remarkably as DPL was reduced (n 5 4). Negative impacts of CM on IgG and protein content of colostrum have been reported in the literature (Brandon and Lascelles, 1975;Remond et al, 1997b;Rastani et al, 2005). Guy et al (1994) demonstrated that prepartum milking of udder halves resulted in less concentration of IgG 1 in secretions of milked glands than in dry glands from 10 days prepartum to 1 day postpartum.…”
Section: Altered Dry Periodsmentioning
confidence: 89%
“…In two studies by our laboratory, no change in lactose concentration of milk was detected during late gestation . Postpartum lactose percentage was unchanged (Andersen et al, 2005;Annen et al, 2007 and or decreased (Remond et al, 1992 and1997a;Rastani et al, 2005) following CM or SDP. Alterations in milk ions (K 1 , Na 1 and Cl 2 ) occur in late gestation when cows are milked throughout the lactation.…”
Section: Impact On Milk Yieldmentioning
confidence: 92%
See 1 more Smart Citation
“…Thus the 16% of respondents that provide a short non-lactating period may have compromised colostrum quality (Rastani et al, 2005), and less time to increase cow BCS reserves. Extra-large farms were less likely to use a target BCS, possibly due to the increased time resources required to individually assess each cow.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the BHBA, NEFA, calcium, IGF-1 blood concentration and the changes of the back fat thickness, a clear interference of the milking regimen could be shown. An improvement of the metabolic condition is also assessed in other studies (Rastani et al, 2005;Schlamberger et al, 2010). Andersen et al (2005) proves in his trial by milking 14 HolsteinFriesian cows continuously that those cows show considerably lower BHBA and NEFA blood concentrations than the 14 cows of the test group with a 7-week drying-off period.…”
Section: Discussionmentioning
confidence: 99%